ENGLISH TEACHERS QUESTIONS IN PROMOTING STUDENTS THINKING SKILL IN SMK NEGERI 10 MEDAN - Sharon Dinda N.H; Sumarsih Sumarsih (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2021)
This study deals with teachers’ questions in promoting students’ thinking skill. The objectives of this study were to reveal the types of questions based on taxonomy that teachers used in classroom communicative practices and how the teachers employed strategies to stimulate students’ responses towards the teachers’ questions. A descriptive qualitative design was used in this study. The data was collected by observing two teachers in two classes of grade twelve. The findings of this study showed that the teachers used all of questions types. The type of teachers’ questions which were commonly used by the two teachers is Productive Questions. The cognitive domain which can be achieved from productive categories is creating level. Teacher A mostly used evaluative question. The cognitive domain which can be achieved from evaluative category is evaluating level. While, Teacher B mostly used productive questions. The cognitive domain which can be achieved from productive category is creating level. Furthermore, the less questions appearing is Empirical Question. So, the researcher can conclude that teachers’ questions can promote higher order questions instead of lower order questions. In addition, the two teachers used some strategies to stimulate students’ responses towards the teachers’ questions. Teacher A used rephrasing strategy, simplification strategy, decomposition strategy, and probing strategy, while Teacher B used rephrasing strategy, repetition strategy, and decomposition strategy.Keywords : Teachers Questions, Cognitive Domain, Question Strategy